Pengaruh Latihan Plyometrics Terhadap Kecepatan Tendangan Sabit Pada Atlet Pencak Silat - Anggi Satria; Tjung Hauw Sin; Ishak Aziz; Suwirman Suwirman (Universitas PGRI Palembang, 2021)
The problem in this study is the low speed of the crescent-kick speed of the pencak silat athletes at the Pat Ban Bu Air Tawar college. The purpose of this study was to determine the effect of plyometrics training on sickle kick speed in pencak silat athletes at the Pat Ban Bu Air Tawar college. This type of research is a quasi experiment. The population in this study were 10 athletes of pencak silat at the Pat Ban Bu Air Tawar college. The sampling technique in this study used a total sampling technique. Many samples in this study amounted to 9 athletes. To obtain data, measurements were taken twice, namely pre-test and post-test. Data were collected by carrying out a sickle kick speed test. The data were analyzed using the mean difference test (t test). The results of this study indicate that: The results of the hypothesis test of the effect of plyometrics training are significant on the speed of the sickle kick in pencak silat athletes at the Pat Ban Bu Air Tawar college, by testing the sickle kick speed hypothesis, the value of tcount = 4.39> ttable = 1.85 The average pre-test was 24.44 and the post-test was 25.89 with a significant level of Î± = 0.05.